2022
DOI: 10.1007/s00392-022-02032-z
|View full text |Cite
|
Sign up to set email alerts
|

Deferral of non-emergency cardiac procedures is associated with increased early emergency cardiovascular hospitalizations

Abstract: Background During the COVID-19 pandemic, in anticipation of a demand surge for high-care hospital beds, many hospitals postponed non-emergency interventions of cardiac patients. Aim The aim of this study was to assess the outcomes of cardiac patients whose non-emergency interventions had been deferred during the COVID-19 pandemic. Methods Patients whose non-emergency cardiac intervention had been cancelled between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Additionally, compared to the control group from 2019, the incidence of cardiac emergency admissions was significantly higher during the post-lockdown phase and increased by almost 52%, suggesting that indeed patients who did not keep their non-emergency appointment during lockdown might have been admitted by the emergency medical services due to an acute cardiac event later on. This thesis is supported by a previous study showing that deferred cardiac patients, despite being classified as postponable, were associated with increased emergency hospitalization and progression of symptoms within the first 365 days [ 27 ].…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, compared to the control group from 2019, the incidence of cardiac emergency admissions was significantly higher during the post-lockdown phase and increased by almost 52%, suggesting that indeed patients who did not keep their non-emergency appointment during lockdown might have been admitted by the emergency medical services due to an acute cardiac event later on. This thesis is supported by a previous study showing that deferred cardiac patients, despite being classified as postponable, were associated with increased emergency hospitalization and progression of symptoms within the first 365 days [ 27 ].…”
Section: Discussionsupporting
confidence: 66%
“…Although the direct quantification of the impact of hospitalizations due to COVID-19 on lost productivity costs and absenteeism is not yet available, the impact of COVID-19 on the global economic and financial markets has been significant, with reductions in income and a rise in unemployment [ 31 ]. Furthermore, RDV reduces the number of days in hospital and thus increases the capacity in the ICU by freeing up bed space [ 32 , 33 ]. Not only does this allow patients to return to work faster following discharge from hospital, but this may also aid in offsetting losses in revenue due to reduced elective surgeries [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study 19 in our review reported that 8.5% of centers to experience adverse patient outcomes as a result of postponing elective procedures. A case–control study that evaluated the effect of deferral of nonemergency cardiac procedures during the pandemic revealed increased emergency early cardiovascular hospitalizations in patients whose elective procedures were deferred during the pandemic compared to the control group 40 . Subgroup analysis revealed that valvular heart disease patients were particularly susceptible to adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%